Clinical Importance of Vamana Karma in Tamakshwasa: A Review - Sahebrao Kadam1 , Shweta Parwe2 , Milind Nisargandha3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Vamana Karma (medicated emesis) is the act of eliminating the vitiated Kapha through the mouth. VamanaKarma is the internal purificatory practice described in Ayurveda which helps to clean the body of excessamount of the vitiated Kapha, Pitta Doshas consecutively. Tamak Shwas means a state in which a sense ofdarkness prevails due to movement of Prana Vayu in wrong direction. It is a disease in which the patientexperience severe symptoms of respiratory distress resemble like Bronchial asthma. Bronchial asthma isa syndrome of variable airflow obstruction. Vamana is the first line of treatment for Utkleshitavastha ofTamakshwasa. In Ayurveda, Shaman and Shodhana treatment is mentioned. We can’t deny the importanceof Vamana Karma in Tamakshwasa, because Kapha is the foremost Dosha that needs to be taken care of thanothers. In this article an attempt has been made to search the research works conducted on Vamana Karmarelated to Tamakshwasa and to establish its role in TamakshwasaData Source: The related data were collected from various research article from the years 2011 – 2019 andfrom the classical texts Charak samhita, Sushrut samhita and Astang hrudaya Observations: Total 16 variousreaserches found and overall outcome is vamanakarma is effective in tamakshwasa. Vamanakarma is veryeffective in tamakshwasa in utkleshavastha because kaphadosha can easily eliminate from body